2014
DOI: 10.3748/wjg.v20.i48.18070
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and proinflammatory cytokines, the key mediators in the pathogenesis of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a condition in which excess fat accumulates in the liver of a patient with no history of alcohol abuse or other causes for secondary hepatic steatosis. The pathogenesis of NAFLD and nonalcoholic steatohepatitis (NASH) has not been fully elucidated. The "two-hit" hypothesis is probably a too simplified model to elaborate complex pathogenetic events occurring in patients with NASH. It should be better regarded as a multiple step process, with accumulation of liver fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
195
2
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(239 citation statements)
references
References 275 publications
9
195
2
11
Order By: Relevance
“…27 TNF-α causes impaired insulin-derived peripheral uptake of glucose by increasing the serine phosphorylation of insulin receptor substrate 1 (IRS-1) and consequently inhibits the translocation of glucose transporter type 4 (GLUT4) to the plasma membrane, which results in peripheral IR. 28,29 Some studies have suggested that treatment with anti-TNF-α antibody can improve insulin sensitivity in IR patients 30,31 . IL-6 is another inflammatory adipokine that is involved the pathogenesis of IR.…”
Section: Discussionmentioning
confidence: 99%
“…27 TNF-α causes impaired insulin-derived peripheral uptake of glucose by increasing the serine phosphorylation of insulin receptor substrate 1 (IRS-1) and consequently inhibits the translocation of glucose transporter type 4 (GLUT4) to the plasma membrane, which results in peripheral IR. 28,29 Some studies have suggested that treatment with anti-TNF-α antibody can improve insulin sensitivity in IR patients 30,31 . IL-6 is another inflammatory adipokine that is involved the pathogenesis of IR.…”
Section: Discussionmentioning
confidence: 99%
“…Given that higher basal levels of TNF-a represent a risk factor in the development and progression of NAFLD (4), the significant decline of TNFa after consumption of ancient khorasan is promising. The significant decrease in IL-1Ra following the consumption of ancient khorasan products is potentially relevant in secondary prevention, given that higher levels of IL-1Ra are reported to be positively related to obesity and the progression of the disease in human subjects (4). Of great interest is that the significant decrease in proinflammatory cytokines, evident in the ancient khorasan group, occurred independently of the significant decreases in percentage fat mass, steatosis grading, and ROS production, evident for both the ancient khorasan and control groups.…”
Section: Liver Steatosis Grading and Doppler Ultrasound Examinationmentioning
confidence: 99%
“…Multiple parallel factors, including insulin resistance, oxidative stress, inflammation, and altered gut microflora, acting synergistically (multiple-hit hypothesis) in genetically predisposed individuals, are implicated in the development and progression of the disease (1,4). Moreover, there is growing evidence that NAFLD is a multisystem disease affecting extrahepatic organs and regulatory pathways, as in T2DM and cardiovascular disease (CVD), with the latter being responsible for the majority of NAFLD deaths (3).…”
Section: Introductionmentioning
confidence: 99%
“…Adipokines are adipose tissue-derived polypeptides with biological activities, which are responsible for all pathological processes of NAFLD, including insulin resistance, steatosis, inflammation, and fibrosis [6,7]. It has been well documented that conventional adipokines, such as adiponectin and leptin, exert antagonistic effects and closely correlate with NAFLD [8][9][10].…”
Section: Introductionmentioning
confidence: 99%